Microbiological evaluation of isolated compounds from the bark of Maytenus guianensis Klotzsch ex Reissek (Celastraceae) - Lima, Renato Abreu; Bay-Hurtado, Fernanda; Meneguetti, Dionatas Ulises de Oliveira; Facundo, João Bezerra; Militão, Júlio Sancho Linhares Teixeira; Matos, Najla Benevides; Facundo, Valdir Alves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Maytenus guianensis Klotzsch ex Reissek is a brazilian Amazon plant widely used in tradicional medicine to treat malaria, leishmaniasis and cancer. Due to the increasing number of resistant strains of microorganisms to known antimicrobial substances, various extracts of medicinal plants are being assayed with the purpose of developing new compounds with antimicrobial activities. Thus, the present work aimed to evaluate the biological potential of isolated substances of the bark of M. guianensis on bacteria. The barks were collected at the Reserva Florestal Adolpho Ducke, in Manaus-AM. After, they were dried and grinded, being subjected to Soxhlet extraction with different solvants according to their polarity degree. The isolated substances were diluted with DMSO 2 %, and for the evaluation of the antibacterial potential, the agar well diffusion technique was used. The design was totally randomized with two replicas per treatment. The evaluation consisted on measuring bacteria colonial growth after 24 hours of the beginning of the experiment. The results obtained from the isolated substances of M. guianensis presented inhibitory effect against at least four out of the five bacteria tested, where satisfactory inhibition halos were noted. The results highlight the antimicrobial potential of this plant, which may be promising for the development of new drugs.